Analysis of Factors Determining Consumer Decisions in Choosing JNE Manggelewa Expedition Services, Dompu District - Apriani, Suci; Irwansyah, Irwansyah; Sumarn, Sumarn (Business Management, 2025)
The increasing number of Indonesians choosing to shop online has had a direct impact on logistics service providers due to the high demand for package deliveries. As a result, many businesses are competing to establish ventures in the logistics sector.The aim of this study is to analyze the determining factors behind consumer decisions in selecting JNE Manggelewa, Dompu Regency, as their preferred courier service. This research adopts a qualitative approach, which seeks to explore and understand the meaning that individuals or groups assign to a particular phenomenon or human-related issue.In analyzing the factors influencing consumer decisions in choosing a courier service, the study also considers the growing competition in the logistics industry, with new companies emerging that offer more competitive prices and innovative services. This has led to a decline in the volume of shipments handled by JNE Manggelewa, as customers begin switching to other courier services that better suit their needs. This study employs data collection techniques such as observation, semi-structured interviews, and documentation. The research involves four key informants who provide essential insights for the study.The findings indicate that consumers’ decisions to choose JNE are influenced by a combination of rational and emotional factors, as well as social influences from those around them. JNE has successfully built a strong position in the minds of consumers by prioritizing service quality, punctuality, and the security of packages, ultimately enhancing customer loyalty in Manggelewa.